Daridorexant, a New Dual Orexin Receptor Antagonist to Treat Insomnia Disorder. Issue 3 (5th February 2020) - Dauvilliers, Yves; Zammit, Gary; Fietze, Ingo; Mayleben, David; Seboek Kinter, Dalma; Pain, Scott; Hedner, Jan
Abstract : Objective: To evaluate the dose–response relationship of daridorexant, a new dual orexin receptor antagonist, on sleep variables in subjects with insomnia disorder. Methods: Adults (≤64 years) with insomnia disorder were randomized (1:1:1:1:1:1) to receive daily oral placebo, daridorexant (5, 10, 25, or 50mg), or 10mg zolpidem for 30 days. The primary efficacy outcome was the change in wake time after sleep onset from baseline to days 1 and 2. Secondary outcome measures were change in latency to persistent sleep from baseline to days 1 and 2, change in subjective wake time after sleep onset, and subjective latency to sleep onset from baseline to week 4. Safety was also assessed. Results: Of 1, 005 subjects screened, 359 (64% female) were randomized and received ≥1 dose. A significant dose–response relationship (multiple comparison procedure‐modeling, 2‐sided p < 0.001) was found in the reduction of wake after sleep onset and latency to persistent sleep from baseline to days 1 and 2 with daridorexant. These reductions were sustained through to days 28 and 29 ( p = 0.050 and p = 0.042, respectively). Similar dose‐dependent relationships were observed for subjective wake after sleep onset and subjective latency to sleep onset. The incidence of treatment‐emergent adverse events was 35%, 38%, 38%, and 34% in subjects treated with 5, 10, 25, and 50mg daridorexant, respectively, compared with 30% for placebo, and 40% for 10mg zolpidem. There were no clinically relevant treatment‐related serious adverse events. Four subjects withdrew due to adverse events. Interpretation: Daridorexant induced a dose‐dependent reduction in wake time after sleep onset in subjects with insomnia disorder (Clinicaltrials.gov NCT02839200). Ann Neurol 2020;87:347–356